2013
DOI: 10.3390/ijms14047923
|View full text |Cite
|
Sign up to set email alerts
|

Identification of O-glycosylated Proteins That Are Aberrantly Excreted in the Urine of Patients with Early Stage Ovarian Cancer

Abstract: Cancer is known to induce or alter the O-glycosylation of selective proteins that may eventually be excreted in the patients’ urine. The present study was performed to identify O-glycosylated proteins that are aberrantly excreted in the urine of patients with early stage ovarian cancer (OCa). These urinary glycoproteins are potential biomarkers for early detection of OCa. In this study, urinary proteins of patients with early stage OCa and age-matched OCa negative women were subjected to two-dimensional gel el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…These findings demonstrated that the glycopatterns, especially the glycopatterns modified by Gal/GalNAc, were decreased as occurred in renal insufficiency. Inoue et al reported the global reduction of the binding to lectins in urine samples of DN at macroalbuminuria stage [30]. Our finding further clarified that glycopatterns showed global reduction when occurring in renal insufficiency in stage of overt proteinuria.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These findings demonstrated that the glycopatterns, especially the glycopatterns modified by Gal/GalNAc, were decreased as occurred in renal insufficiency. Inoue et al reported the global reduction of the binding to lectins in urine samples of DN at macroalbuminuria stage [30]. Our finding further clarified that glycopatterns showed global reduction when occurring in renal insufficiency in stage of overt proteinuria.…”
Section: Discussionsupporting
confidence: 77%
“…Abnormal glycosylation of certain glycoprotein in urine could be a more sensitive biomarker for disease diagnosis and monitoring. It is reported that aberrantly excreted urinary O -glycosylated proteins (clusterin, leucine-rich alpha-2-glycoprotein, and kininogen) could serve as potential biomarkers for the early detection of early stage ovarian cancer [30]. As a powerful tool, lectin microarray was used to investigate the glycopatterns of protein for decades.…”
Section: Discussionmentioning
confidence: 99%
“…Although its mechanistic role remains unclear in cancer, KNG1 could have antiangiogenic properties and inhibitory actions on proliferation of endothelial cells [44]. Previous studies have shown lower levels of KNG1 in urine or sera of ovarian carcinoma cases and cervical cancer patients respectively [45, 46]. But in these studies the protein detected was KNG1 light chain and not the entire protein.…”
Section: Discussionmentioning
confidence: 99%
“…Time-of-flight spectra were generated by averaging 60 laser shots and collected in the positive mode at laser intensity 185 and detector sensitivity 8 with molecular weight optimized from 2,000 to 10,000 Da (15). Mass accuracy was calibrated on the day of measurements before data collection using the All-in-one peptide molecular mass standard (8).…”
Section: Methodsmentioning
confidence: 99%
“…BPS was also used to perform a 10-fold crossvalidation because the size of the data set was too small for an independent validation set. This process allows the sensitivity and specificity to be predicted for future data and provides an accurate estimate of the predictive accuracy of the selected decision tree (7,13,15).…”
Section: Peak Detection Data Analysis and Decision Tree Classificationmentioning
confidence: 99%